Agents of soil salinization in “Chervlenoe” and “Duboovrazhniy” plots of the Svetloyarsk irrigation system - E. I. Kravchenko (Бюллетень Почвенного института им. В.В. Докучаева, 2019)
The agents that determine the soil salinity of the key plots “Chervlenoe” and “Duboovrazhniy” of the Svetloyarsk irrigation system (Volgograd region) are studied. We carried out a multifactor analysis of the toxic salts amount variance depending on the following agents: relief, vegetation, parent material and irrigation method, the water extract (1 : 5) being used. It was found that the factors determining the degree of soil salinity in terms of the amount of toxic salts in both cases is parent material. Its contribution into the total variance was more than 80 % for both studied plots. On the plot “Duboovrazhniy” relief also turned out to be a significant factor. Anthropogenic factor – the method of irrigation – was insignificant. The graphs of cumulative frequencies of the occurrence of salinity levels were constructed for soil layers of 0–30 cm, 30–100 cm, 100–150 cm, 150–200 cm. The top soil layer of 0–30 cm is almost non-saline in both areas. On the “Chervlenoe” plot there are strong and very strong degrees of soil salinization; in general, this site is characterized by higher toxic salts amount compared to the “Duboovrazhniy” plot.